Caracterización morfológica y fenológica en tomate de árbol (Solanum betaceum Cav.) en la Quinta Experimental Docente la Argelia de la Universidad Nacional de Loja - Cartuche Morocho, Vilma Andrea (2024)
The tree tomato (Solanum betaceum Cav.) is native to the Andean region in Ecuador, this crop presents a valuable economic opportunity. However, despite its importance, it is still considered a marginalized specie. In the province of Loja, there is very little information regarding morphological and phenological characterization. This research was conducted at the Quinta Experimental Docente La Argelia of the National University of Loja. The objectives were to morphologically characterize ten accessions of tree tomato and determine the phenological phases of tree tomato under the climatic and soil conditions of the Loja valley. A total of 100 plants (10 plants per ecotype) were studied. For characterization, the morphological descriptor for tree tomato was used, covering stems, leaves, fruits, seeds, and flowers from Biodiversity International. A database was created, and multivariate cluster analysis (dendrogram) was applied for quantitative characters, along with correspondence analysis for qualitative characters. An analysis of variance (ANOVA) with Tukey’s test at 95% significance level was conducted to determine differences between growth variables and quantitative traits. In this study, good yields were obtained based on the coefficient of variation (CV > 20%). The most important descriptors included tree crown diameter (46.04 cm), number of fruits per plant (63.07), fruit weight (117.54 g), and number of seeds per fruit (22.94). Regarding cluster analysis, Cluster 3, composed of the purple or black ecotype, showed good averages in terms of plant architecture, fruits, and seeds. In terms of phenology, the purple or black and elliptical yellow ecotypes exhibited earlier behavior (463 days) from transplant to fruit maturity. There were differences between the following growth variables: the purple or black ecotype 1 obtained better results in terms of plant height (2,67 cm), trunk diameter (6,90 cm), leaf length (17,67 cm), and leaf width (16,04 cm). However, the ecotype 3 (common red rcsps) obtained a better average of young leaves (24,60).